Eckhart, Aquinas, and the Problem of Intrinsic Goods. Issue 1 (2nd January 2019) - Chua, Reginald Mary
ABSTRACT: I discuss Eckhart's and Aquinas' conception of human-divine union with reference to what I call the problem of intrinsic goods, a problem concerning how to reconcile the pursuit of actions which are prima facie sought for their own sake (e.g. pursuing justice for the marginalized, listening to a work of music) with the pursuit of God as the ultimate end of every action. I introduce the problem with the help of Germain Grisez's critique of Aquinas' account of union with God, and I suggest that Eckhart's alternative conception of union may be understood as an attempt to resolve (or dissolve) the problem.